Más allá de la narrativa publicitaria: Josefinas y sus productos de storytelling - Dias, Liliana (2021)
In the last few years, advertising narratives have become increasingly important. Facing an environment of fierce competition and communication overload, brands needed to reinvent their communication strategies, and stories became protagonists, particularly in the digital environment. This article addresses a new way of applying storytelling in marketing, which is using it to extend products. In our theoretical framework, we review the general importance of storytelling as a communication tool and strategy, departing from the notion of storytelling as the essence of human communication (Fisher, 1987). As empirical work, we present the case study of Josefinas, a Portuguese luxury handmade shoe brand. For each new product, the brand presents a story that not only explains the inspiration for the product, but also communicates values, a lifestyle, emotions, and inspires. We studied a sample of communication pieces and applied a thematic matrix (Kuckartz, 2014), with coding categories inspired by storytelling models and also by brand equity (Aaker, 1991) and product extension (Kotler and Keller, 2012) models. In our findings, we stress the originality of the brand in going beyond advertising in its use of narratives, applying it to add layers of meaning to their products, which are reflected in the brand image, and even in its equity. Thus, we conclude by suggesting the concept of ‘product narratives’.